2018
DOI: 10.3390/robotics7020025
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Systems for Estimating Visual Attention in Robot-Assisted Therapy of Children with Autism and Intellectual Disability

Abstract: Recent studies suggest that some children with autism prefer robots as tutors for improving their social interaction and communication abilities which are impaired due to their disorder. Indeed, research has focused on developing a very promising form of intervention named Robot-Assisted Therapy. This area of intervention poses many challenges, including the necessary flexibility and adaptability to real unconstrained therapeutic settings, which are different from the constrained lab settings where most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 61 publications
0
54
0
Order By: Relevance
“…al. [4] had reported that from ABIDE dataset brain morphometric features were derived with the help of FreeSurfer and were applied on 3 classifiers namely Random Forest (RF), Support Vector Machine (SVM) and Gradient Boosting Machine (GBM). Experiments were conducted on datasets of individual sites and were showing higher accuracy of 97%.…”
Section: A Machine Learning Algorithmsmentioning
confidence: 99%
“…al. [4] had reported that from ABIDE dataset brain morphometric features were derived with the help of FreeSurfer and were applied on 3 classifiers namely Random Forest (RF), Support Vector Machine (SVM) and Gradient Boosting Machine (GBM). Experiments were conducted on datasets of individual sites and were showing higher accuracy of 97%.…”
Section: A Machine Learning Algorithmsmentioning
confidence: 99%
“…In many cases, cognitionenhanced robot learning ability is required. In some scenarios, robots are expected to work together with human beings, where compliant performance and human-friendly user experience are desired, e.g., [2], [3]; while in others, robots are expected to autonomously conduct tasks like human beings, e.g., [4]. By using game theory and policy iteration, the human being's control objective can be estimated in the human-robot interaction process [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of ASD therapy, SAR has shown great advances and potential benefits in the development and applications of therapies for CwASD [6][7][8][9]. Specifically, SAR has been used to assist the diagnostic process and practice and improve social skills, such as eye contact and joint attention [10,11], emotion recognition [12,13], imitation [14], sharing simple activities, and increasing self-initiated interaction [15] to encourage basic verbal and nonverbal communication [16].…”
Section: Introductionmentioning
confidence: 99%